2020
DOI: 10.21203/rs.3.rs-32706/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial Distribution and Modeling of malnutrition among under-five Children in Ethiopia

Abstract: Background Majority of this world is concerned by malnutrition. Ethiopia is one of the Sub Saharan African countries known by poverty, childhood diseases, high mortality and poor infrastructures and technology. The study aimed to examine differences within individuals and between clusters in nutritional status of under-five children and to identify socioeconomic factors using adequate nutrition of children in Ethiopia. Method: Data was obtained from Ethiopian 2019 Mini Demographic and Health Survey surveyed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 7 publications
3
6
0
Order By: Relevance
“…But it was higher than studies conducted in Tanzania [ 56 ], in Kenya [ 54 ], in Ghana [ 57 ], and in Senegal [ 58 ]. This finding was also in line with studies conducted in different parts of Ethiopia previously [ 27 ]. This finding for wasting is lower when compared with studies conducted in Ethiopia [ 59 ], in Senegal [ 58 ], and Cameroon [ 55 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…But it was higher than studies conducted in Tanzania [ 56 ], in Kenya [ 54 ], in Ghana [ 57 ], and in Senegal [ 58 ]. This finding was also in line with studies conducted in different parts of Ethiopia previously [ 27 ]. This finding for wasting is lower when compared with studies conducted in Ethiopia [ 59 ], in Senegal [ 58 ], and Cameroon [ 55 ].…”
Section: Discussionsupporting
confidence: 93%
“…A study conducted previously reported that significant clustering of wasting across regions. Thus, Afar and Somali regions were identified as hot spot areas for wasting [ 27 ]. A study conducted on spatial clustering of stunting and wasting in Meskane Mareko District in Gurage Zone found significant clustering of wasting in Diram and Bati Lejano kebeles of the district [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The distribution of undernutrition various across the country. It is concentrated among rural residents and poor societies [ 20 ]. Literatures indicate that undernutrition varies across region and geographic areas [ 9 , 21 ].…”
Section: Introductionmentioning
confidence: 99%